Managing Puputan Badung Storynomics in Denpasar City Tours - I Gde Hendra Narottama; I Gede Mudana; Ni Gst Nym Suci Murni; Ni Putu Somawati (International Journal of Glocal Tourism, 2022)
Purpose: This study aims to determine the management implementation of the Storynomics concept of the Puputan Badung war in the city tours of Denpasar and determine the management implementation model that can be used. Research methods: The data collection methods used are interviews, participatory observations, documentation, and focus group discussions. Findings: Storynomics tourism as one of the concepts echoed by the current government in its aim to promote historical and heritage stories in tourist destinations has been eyed to begin developing in each region in Indonesia. Denpasar City has started to adopt the concept of storytelling in packaging historical stories, but the synergy built between each stakeholder has not been optimal. Implication: Good cooperation is needed between each related party in developing the concept of storynomics tourism in a sustainable manner in the future.